The Amsterdam petunia germplasm collection: A tool in plant science - Strazzer, Pamela; Verbree, Bets; Bliek, Mattijs; Koes, Ronald; Quattrocchio, Francesca M. (Frontiers in Plant Science, 2023)
Petunia hybrida is a plant model system used by many researchers to investigate a broad range of biological questions. One of the reasons for the success of this organism as a lab model is the existence of numerous mutants, involved in a wide range of processes, and the ever-increasing size of this collection owing to a highly active and efficient transposon system. We report here on the origin of petunia-based research and describe the collection of petunia lines housed in the University of Amsterdam, where many of the existing genotypes are maintained.